Wykorzystanie modeli partnerstwa publiczno-prywatnego w procesie finansowania mieszkalnictwa - Maciejasz-Świątkiewicz, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents different models of public-private partnership (PPP) that can be used in housing financing process. It is divided into 3 parts plus introduction and conclusion. First part explains the idea of PPP and its importance. Second one shows the models and their suggested usage. And the third one deals with problem of suitability of housing activities and PPP models. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 143-150